Sacrificial anode material and preparation method thereof

By using the combination of rare earth elements and metal elements in the magnesium alloy sacrificial anode material and the combination of functional enhancers, the problems of self-corrosion and low current efficiency of the magnesium alloy sacrificial anode material are solved, and efficient electrochemical protection and long life of the material are achieved.

CN119900031APending Publication Date: 2025-04-29GUANGZHOU KRYSTIC BUILDING MATERIALS CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202510206735.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing magnesium alloy sacrificial anode materials have problems of self-corrosion and low current efficiency in electrochemical environments, resulting in unsatisfactory protection and accelerated material consumption.

Method used

Through the combination of rare earth elements and metal elements, zinc, titanium, indium, cerium, lanthanum, gadolinium and other elements are used to combine functional strengthening agents such as nitrogen-doped spiral carbon nanofibers and carbon nanotubes to form an efficient conductive network and protective film to optimize the structure and electrochemical properties of the material.

Benefits of technology

It significantly improves the current efficiency of the material, reduces the occurrence of self-corrosion reactions, extends the service life of the anode material, and improves the protection effect on the protected metal.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of alloys, in particular to a sacrificial anode material and a preparation method thereof. The material comprises the following components in parts by weight: 3.24 to 7.28 parts of zinc, 1.22 to 3.43 parts of titanium, 0.54 to 1.27 parts of indium, 0.22 to 0.64 part of cerium, 0.36 to 0.77 part of lanthanum, 1.10 to 2.47 parts of gadolinium, 5.47 to 11.21 parts of a function enhancer and the balance of magnesium, the function enhancer is a helical carbon nanofiber doped with a carbon nano tube. The material provided by the invention does not contain aluminum metal, so that the generation of a reticular Mg17Al12 phase is avoided, the occurrence of a self-corrosion reaction is reduced, and the current efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloys, and in particular relates to a sacrificial anode material and a preparation method thereof. Background Art

[0002] The economic losses caused by the corrosion of metal materials are huge. The use of sacrificial anodes for electrochemical protection is an effective method to prevent the corrosion of metal materials, which is of great significance to the improvement of the corrosion resistance of metal materials and the extension of their service life. Magnesium alloys have good electrochemical properties and are often used as sacrificial anode materials to protect the cathode materials of equipment and devices to extend the service life of the cathode materials. The main function of the sacrificial anode is to protect the protected metal structure by its own preferential corrosion (oxidation). This requires that the electrode potential of the sacrificial anode material be sufficiently negative so that a sufficiently large potential difference can be formed between the anode material and the protected metal in the electrolyte environment. In this way, it can be ensured that the anode material undergoes an oxidation reaction as an anode, and the protected metal undergoes a reduction reaction as a cathode, thereby avoiding the corrosion of the protected metal. Similarly, high current efficiency is also one of the requirements. Current efficiency refers to the ratio of the actual current output of the sacrificial anode to the current theoretically calculated according to Faraday's law. High current efficiency means that during the anode dissolution process, more electricity is used to protect the protected metal instead of being wasted due to other side reactions (such as self-corrosion, hydrogen evolution, etc.). This helps to provide a stable protection current for a long time, reduce the consumption rate of the anode material, and improve the protection effect and the economy of the anode material. In addition, the sacrificial anode material needs to have a certain chemical and electrochemical stability in the use environment. This means that it will not lose its anode protection function due to reactions with other chemicals in the electrolyte solution. At the same time, in the long-term electrochemical process, its electrode performance (such as potential, current output, etc.) should remain relatively stable and will not fluctuate due to changes in the material itself.

[0003] For example, CN107142483A discloses a multi-component magnesium alloy sacrificial anode material containing Sm and a preparation method thereof. The presence of aluminum in this application can improve the anodic dissolution behavior of the magnesium alloy. In the absence of aluminum, the anodic dissolution process of the magnesium alloy may become uneven and prone to local corrosion. This will lead to more side reactions, such as the intensification of the hydrogen evolution reaction. The hydrogen evolution reaction consumes the electrons generated by the anodic dissolution of the magnesium alloy, which reduces the current actually used for cathodic protection and reduces the current efficiency. In addition, aluminum has the function of regulating the electrode potential in the magnesium alloy sacrificial anode material. The electrode potential of magnesium itself is very negative, but in an actual corrosion environment, without the regulation of elements such as aluminum, a passivation film is easily formed on its surface. This passivation film will cause the potential of the magnesium alloy to shift positively, resulting in a decrease in the potential difference between the magnesium alloy and the protected metal. A sufficient potential difference is a key factor in the function of the sacrificial anode material. Insufficient potential difference will reduce the protection current and make it impossible to effectively perform cathodic protection on the protected metal.

[0004] For example, CN101818351A discloses a high negative potential magnesium-based alloy sacrificial anode material and its application. Most of the application is magnesium. In fact, the chemical properties of magnesium alloys are active and the electrode potential is very negative, which makes it have strong reducibility in electrolyte solutions. Even when used as a sacrificial anode to protect other metals, magnesium alloys themselves are prone to corrosion reactions. Its self-corrosion is mainly due to the reaction of magnesium with water to generate magnesium hydroxide and hydrogen. This reaction may be more intense in some environments, resulting in faster consumption of magnesium alloys than expected. In addition, during the anodic dissolution process, magnesium alloys are prone to side reactions in addition to generating effective current for protecting the protected metal. The most important side reaction is the hydrogen evolution reaction, that is, the magnesium alloy reacts with hydrogen ions in the electrolyte solution to generate hydrogen. This process consumes a portion of the electrons generated by the dissolution of the magnesium alloy, which reduces the proportion of the effective current actually used for cathodic protection to the total current (current efficiency).

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a sacrificial anode material and a preparation method thereof. The material provided by the present invention does not contain aluminum metal, thereby avoiding the mesh Mg 17 Al 12 phase, reduces the occurrence of self-corrosion reaction, and improves current efficiency.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: In a first aspect, an embodiment of the present invention provides a sacrificial anode material, comprising the following components in parts by weight: 3.24-7.28 parts of zinc, 1.22-3.43 parts of titanium, 0.54-1.27 parts of indium, 0.22-0.64 parts of cerium, 0.36-0.77 parts of lanthanum, 1.10-2.47 parts of gadolinium, 5.47-11.21 parts of a functional enhancer, and the balance being magnesium; The function enhancer is a spiral carbon nanofiber doped with carbon nanotubes.

[0008] In a preferred embodiment, the material includes the following components in parts by weight: 4.24-6.13 parts of zinc, 2.07-2.87 parts of titanium, 0.68-1.05 parts of indium, 0.34-0.48 parts of cerium, 0.42-0.61 parts of lanthanum, 1.58-2.02 parts of gadolinium, 7.45-10.01 parts of functional enhancer, and the balance is magnesium.

[0009] In the present invention, the current efficiency of the material is significantly improved by compounding the rare earth element and the metal element, and the occurrence of the self-corrosion reaction is reduced.

[0010] In terms of improving the current efficiency of materials, zinc can form a solid solution in magnesium alloys. When zinc atoms dissolve into the magnesium lattice, the electrode potential of the magnesium alloy will change. An appropriate amount of zinc can make the potential of the magnesium alloy more negative and maintain it in a suitable range, which is conducive to forming a sufficient potential difference between the protected metal and the sacrificial anode, thereby driving the generation of protective current and improving current efficiency. For example, in a magnesium alloy containing a certain amount of zinc, its electrode potential is more negative than pure magnesium, which can better provide protective current for metals such as steel. And the addition of zinc can inhibit the self-corrosion reaction of magnesium alloys. In the corrosion process of magnesium alloys, self-corrosion will consume magnesium alloys and reduce current efficiency. Zinc can change the properties of the corrosion product film on the surface of magnesium alloys, making this film denser, thereby preventing the corrosive medium (such as dissolved oxygen and chloride ions in water) from further contacting the magnesium alloy matrix, reducing the occurrence of self-corrosion reactions, allowing more magnesium alloys to dissolve to generate protective currents and improve current efficiency. Titanium can be used as a grain refiner in magnesium alloys. During the solidification process of magnesium alloys, titanium can promote nucleation and refine grains. The fine grain structure can make the magnesium alloy dissolve more evenly when used as a sacrificial anode. When the magnesium alloy dissolves evenly, the anodic reaction can be carried out more effectively on the entire anode surface, reducing the side reactions caused by local excessive dissolution, such as hydrogen evolution reaction, thereby improving the current efficiency. And titanium can improve the surface activity of magnesium alloy to a certain extent. It can adsorb on the surface of magnesium alloy, change the arrangement and electronic state of surface atoms, make the anodic dissolution reaction of magnesium alloy in electrolyte solution easier to proceed, and reduce side reactions, which is beneficial to improve the current efficiency. At the same time, indium can adjust the electrode potential of magnesium alloy so that it maintains a suitable potential in the electrolyte environment, which is conducive to the generation of stable protection current. Indium can improve the electrochemical activity of magnesium alloy, making the anodic dissolution reaction of magnesium alloy easier to proceed when used as a sacrificial anode. And indium can form a special protective film on the surface of magnesium alloy, which interacts with the corrosion product film of magnesium alloy itself, making it more stable and protective. It can prevent harmful ions (such as chloride ions) in the electrolyte solution from corroding magnesium alloy, reduce self-corrosion, and thus improve the current efficiency of magnesium alloy for cathodic protection. In addition, in the smelting process of magnesium alloy, cerium can play a role in purifying the melt. It can combine with impurity elements (such as oxygen, sulfur, etc.) in the alloy to form high-melting-point compounds, which can be removed by floating or precipitation, thereby improving the purity of the magnesium alloy. The improvement in purity helps to reduce local micro-battery corrosion caused by impurities, making the organizational structure of the magnesium alloy more uniform, the anode dissolution more uniform, and improving the current efficiency. In addition, cerium can form corrosion-resistant phases with elements such as magnesium in the magnesium alloy. These corrosion-resistant phases are distributed in the alloy matrix and can prevent further corrosion during the corrosion process.The compound formed by cerium and magnesium can act as a barrier on the surface or grain boundary of magnesium alloy, reduce the intrusion of corrosive media, reduce the self-corrosion rate, and increase the effective current ratio for cathodic protection, that is, the current efficiency. Similarly, lanthanum can adjust the electrochemical properties of magnesium alloys and make the electrode potential of magnesium alloys more stable. It can synergize with other elements in magnesium alloys to inhibit the passivation of magnesium alloys in electrolyte solutions. When magnesium alloys are not easy to passivate, their anodic dissolution reaction can continue to proceed effectively and improve the current efficiency. Lanthanum and zinc and other elements work together to keep the potential of magnesium alloys in seawater within a suitable range and ensure stable protection current output. Similar to titanium, lanthanum can also refine the grains of magnesium alloys. Fine grains help improve the corrosion resistance and dissolution uniformity of magnesium alloys. During the corrosion process, magnesium alloys with fine grains can provide protection current more evenly, reduce current loss caused by local corrosion, and thus improve current efficiency. Furthermore, gadolinium can change the electronic structure of magnesium alloys and adjust the electrode potential of magnesium alloys by affecting the chemical bonds between atoms in the alloy and the distribution of electron clouds. Appropriate potential helps magnesium alloys generate sufficient protection current when used as sacrificial anodes. Gadolinium can form an alloy phase with magnesium, change the potential of the alloy phase, make it more conducive to cathodic protection in the electrolyte environment, and improve current efficiency. Gadolinium can improve the thermal stability of magnesium alloys, which is important for the application of magnesium alloys in some environments with large temperature changes. At the same time, gadolinium can also improve the corrosion resistance of magnesium alloys and reduce self-corrosion. When the self-corrosion of magnesium alloys is reduced, more magnesium alloys are used to generate protection current, thereby improving current efficiency. For example, in a high-temperature electrolyte solution, magnesium alloys containing gadolinium can maintain good corrosion resistance and stably provide protection current. The combined action of zinc, titanium, indium, cerium, lanthanum, gadolinium and other elements can optimize the microstructure of magnesium alloys. Elements such as titanium and lanthanum refine the grains, elements such as zinc, indium, and gadolinium adjust the potential, and cerium purifies the melt and forms a corrosion-resistant phase, making the internal structure of the magnesium alloy more uniform and the potential distribution more reasonable. This optimized organization and potential distribution enable the anodic dissolution of magnesium alloys to proceed uniformly and stably when used as sacrificial anodes, thereby improving current efficiency. The synergistic effect of these elements can enhance the corrosion resistance of magnesium alloys. They inhibit self-corrosion and other side reactions (such as hydrogen evolution reaction) by forming a dense surface film, corrosion-resistant phase and reducing impurities. For example, the surface film regulated by elements such as zinc, indium and gadolinium and the corrosion-resistant phase formed by elements such as cerium and lanthanum work together to prevent the invasion of corrosive media and reduce unnecessary consumption of magnesium alloys, thereby improving the current efficiency of magnesium alloys for cathodic protection.

[0011] In terms of reducing the occurrence of self-corrosion reactions, zinc can form a protective film on the surface of magnesium alloys. When magnesium alloys are exposed to a corrosive environment, zinc will preferentially react with the corrosive medium. In an environment containing oxygen and moisture, zinc will oxidize to form zinc oxides and hydroxides. These products can form a relatively dense protective film on the surface of the magnesium alloy, preventing oxygen and moisture from further contacting the magnesium alloy matrix, thereby reducing the self-corrosion reaction. At the same time, zinc can adjust the electrode potential of the magnesium alloy, so that the activity of the magnesium alloy is inhibited to a certain extent. An appropriate amount of zinc can shift the potential of the magnesium alloy to a suitable range, reducing the tendency of the magnesium alloy as an active metal to self-corrode with corrosive media such as water. Titanium plays a role in refining grains in magnesium alloys. In magnesium alloys, grain boundaries are often areas where corrosion is prone to occur, because the atoms at the grain boundaries are irregularly arranged and have higher energy. After titanium refines the grains, the area of ​​the grain boundaries is reduced, thereby reducing the probability of self-corrosion reactions occurring at the grain boundaries. For example, the degree of grain boundary corrosion of magnesium alloys after titanium grain refinement is significantly reduced compared to magnesium alloys without grain refinement. At the same time, titanium can improve the surface state of magnesium alloys. It can form a titanium oxide film on the surface of magnesium alloys, which can prevent the direct contact between the corrosive medium and the magnesium alloy matrix, and can change the electronic structure of the magnesium alloy surface, reduce its surface reaction activity, and thus reduce the occurrence of self-corrosion reactions. Indium can change the properties of the corrosion product film on the surface of magnesium alloys. It can interact with elements such as magnesium and oxygen on the surface of magnesium alloys to form a more stable and dense protective film. Indium can promote the formation of a protective film containing indium compounds on the surface of magnesium alloys, which can effectively prevent the invasion of corrosive ions such as chloride ions and reduce the self-corrosion reaction of magnesium alloys. At the same time, indium can adjust the electrochemical behavior of magnesium alloys and reduce the degree of anodic polarization of magnesium alloys in corrosive environments. In this way, when the magnesium alloy undergoes a corrosion reaction, its self-corrosion current density is reduced, thereby reducing the rate of the self-corrosion reaction. In addition, cerium can purify the alloy melt during the smelting process of magnesium alloys. It can combine with impurity elements (such as oxygen, sulfur, iron, etc.) in magnesium alloys to form high-melting point compounds, which can be removed by floating or precipitation. The reduction of impurity elements can reduce the self-corrosion reaction caused by the formation of micro-batteries between impurities and the magnesium alloy matrix. Cerium can form corrosion-resistant phases with elements such as magnesium in magnesium alloys. These corrosion-resistant phases are distributed in the alloy matrix and can prevent further corrosion during the corrosion process. The compounds formed by cerium and magnesium can act as a barrier on the surface or grain boundaries of magnesium alloys. Once corrosion occurs, these corrosion-resistant phases can slow down the invasion rate of corrosive media, thereby reducing the rate of self-corrosion reactions. Like titanium, lanthanum can also refine the grains of magnesium alloys. When titanium and lanthanum exist at the same time, their synergistic effect on grain refinement is more significant. The refined grains can reduce intergranular corrosion and reduce the self-corrosion reaction of magnesium alloys. In magnesium alloys containing titanium and lanthanum, the grain size can be further reduced, and the sensitivity to intergranular corrosion is also reduced.Lanthanum can react with elements on the surface of magnesium alloys to form a protective film. This protective film works synergistically with the protective film formed by elements such as zinc and indium to enhance the corrosion resistance of magnesium alloys. The protective film formed by lanthanum can fill the tiny pores of other protective films, making them denser, thereby more effectively preventing the invasion of corrosive media and reducing self-corrosion reactions. Gadolinium can improve the thermal stability of magnesium alloys. Under high temperature conditions, magnesium alloys are prone to thermal corrosion, and the presence of gadolinium can reduce this thermal corrosion. For example, in magnesium alloy applications in high temperature working environments such as engine parts, gadolinium can inhibit the self-corrosion reaction of magnesium alloys caused by high temperature oxidation. At the same time, gadolinium can adjust the electronic structure of magnesium alloys, and inhibit the activity of magnesium alloys by changing the chemical bonds and electron cloud distribution between atoms in the alloy. This inhibitory effect can reduce the self-corrosion reaction between magnesium alloys and corrosive media. Gadolinium can shift the self-corrosion potential of magnesium alloys in electrolyte solutions to the positive side, reducing their tendency to self-corrosion. In general, the protective films formed on the surface of magnesium alloys by elements such as zinc, indium, and lanthanum work synergistically with each other. These protective films prevent the intrusion of corrosive media from different angles. For example, the zinc oxide film, the indium compound film and the lanthanum protective film can form a multilayer structure. Each layer of the film has its own unique protective effect. When working together, it can more effectively prevent oxygen, moisture and corrosive ions from contacting the magnesium alloy matrix, thereby reducing the rate of self-corrosion reaction. Titanium and lanthanum refine the grains and reduce the area of ​​the grain boundary, which is a corrosion-sensitive area. At the same time, cerium purifies the alloy to remove impurities and reduce micro-battery corrosion caused by impurities. These measures jointly optimize the organizational structure of the magnesium alloy, reducing the overall self-corrosion sensitivity of the magnesium alloy. In the magnesium alloy treated with these elements, both grain boundary corrosion and corrosion caused by impurities are effectively controlled. Elements such as zinc, indium, and gadolinium regulate the electrochemical properties of the magnesium alloy, optimizing the potential and polarization behavior of the magnesium alloy. They reduce the driving force of the self-corrosion reaction of the magnesium alloy by adjusting the positive potential shift and reducing the degree of anodic polarization, thereby reducing the rate of the self-corrosion reaction.

[0012] In a preferred embodiment, the preparation method of the functional enhancer is as follows: Polyacrylonitrile and N,N-dimethylformamide are mixed and stirred, and then nickel acetate is added for electrostatic spinning to obtain electrostatically spun fibers, and then heat stabilization treatment is performed to obtain a solid phase, and the solid phase is mixed with melamine for a primary reaction, and then acetylene gas is introduced for a secondary reaction, and the functional enhancer is obtained by cooling, washing, grinding and sieving.

[0013] In a preferred embodiment, the mass ratio of polyacrylonitrile, N,N-dimethylformamide and nickel acetate is 1:(50-100):(5-20).

[0014] In a preferred embodiment, the stirring conditions are: stirring temperature is 40-60° C., and stirring time is 3-6 h.

[0015] In a preferred embodiment, the heat stabilization treatment is carried out under the conditions of: keeping the temperature at 200-300° C. for 1-3 hours.

[0016] In a preferred embodiment, the mass ratio of the solid phase to melamine is 1:(1.2-1.9).

[0017] In a preferred embodiment, the conditions of the primary reaction are: reacting at a temperature of 600-800° C. for 1-3 h under an argon atmosphere.

[0018] In a preferred embodiment, the secondary reaction is carried out at a temperature of 700-900° C. for 15-40 min.

[0019] In a preferred embodiment, the sieve used for screening is 100-300 mesh.

[0020] The present invention directly prepares nitrogen-doped spiral carbon nanofibers through electrospinning technology, and in situ generates carbon nanotubes on the nitrogen-doped spiral carbon nanofibers, so that the carbon nanotubes are directly embedded in the surface of the spiral carbon nanofibers, thereby preventing the problems of agglomeration and phase separation of the structures of the two when the two are directly mixed, and further synergizes with various elements to improve the current efficiency of the material and reduce the occurrence of self-corrosion reactions of the material.

[0021] Specifically, carbon nanotubes are very easy to entangle and agglomerate with each other due to their large aspect ratio, high specific surface area and intermolecular forces, forming aggregates at the micron or even millimeter level. Nitrogen-doped spiral carbon nanofibers also have a certain aspect ratio. When the two are simply mixed, this agglomeration phenomenon becomes more serious, making it difficult to achieve uniform dispersion, resulting in large performance differences between the various parts of the material, and unable to give full play to their respective advantages. In addition, the two have different surface energies and chemical activities, and direct mixing is difficult to ensure stable coexistence in the matrix material, and phase separation is prone to occur, resulting in unstable material performance, and the improvement of current efficiency cannot be effectively met. Even due to the unevenness of the material, the rate of occurrence of the self-corrosion reaction of the material increases, and the preparation method of the present invention just overcomes this point.

[0022] In terms of improving current efficiency, carbon nanotubes themselves have excellent electrical properties, such as high conductivity. When it is generated in situ on nitrogen-doped spiral carbon nanofibers, it can build an efficient conductive network. When the magnesium alloy is used as a sacrificial anode for oxidation reaction, the electrons can be quickly transmitted to the protected metal surface through this conductive network. This reduces the resistance loss during electron transmission, allowing the anodic dissolution reaction of the magnesium alloy to proceed more smoothly, thereby improving the effective current ratio used for protection, that is, the current efficiency. At the same time, the nitrogen-doped spiral carbon nanofibers provide a unique growth substrate for carbon nanotubes. This structure can make the carbon nanotubes more evenly distributed on the surface or inside of the magnesium alloy. When the magnesium alloy is used as a sacrificial anode, the uniformly distributed carbon nanotube-nitrogen-doped spiral carbon nanofiber composite can adjust the electric field distribution on the surface of the magnesium alloy, so that the anodic dissolution reaction is carried out more evenly on the entire magnesium alloy surface. The side reactions caused by local excessive dissolution, such as hydrogen evolution reaction, are avoided, thereby improving the current efficiency. And the carbon nanotube-nitrogen-doped spiral carbon nanofiber composite can change the state of the magnesium alloy surface. Magnesium alloys are prone to form a passivation film under certain conditions, which hinders the continuation of the anodic dissolution reaction. The complex can be adsorbed on the surface of the magnesium alloy, preventing the formation of a passive film or destroying the passive film that has been formed, so that the magnesium alloy can continue to undergo an anodic dissolution reaction, thereby improving the current efficiency. The in-situ generated carbon nanotubes have abundant active sites on the nitrogen-doped spiral carbon nanofibers. These active sites can promote the anodic dissolution reaction of the magnesium alloy. The magnesium atoms in the magnesium alloy can more easily lose electrons at these active sites and be converted into magnesium ions to enter the electrolyte solution, thereby improving the electrochemical activity of the magnesium alloy, increasing the effective protection current, and improving the current efficiency.

[0023] In terms of reducing the occurrence of self-corrosion reactions, the carbon nanotubes generated in situ on the nitrogen-doped spiral carbon nanofibers can form a physical barrier on the surface of the magnesium alloy. This barrier can prevent the corrosive medium (such as oxygen, water and corrosive ions in the electrolyte) from directly contacting the magnesium alloy matrix. It is like putting a layer of protective clothing on the magnesium alloy, reducing the influence of external factors that trigger the self-corrosion reaction. At the same time, the presence of the carbon nanotube-nitrogen-doped spiral carbon nanofiber composite can adjust the surface potential of the magnesium alloy. By changing the surface potential of the magnesium alloy, it tends to be more stable, reducing the tendency of the magnesium alloy surface to self-corrode as an anode. This potential regulation effect is similar to setting a buffer zone for the electrochemical corrosion reaction of the magnesium alloy, making it less likely to spontaneously self-corrode. And the composite can interact with the protective film (such as magnesium oxide or hydroxide film) naturally formed on the surface of the magnesium alloy to enhance the stability of the protective film. It can fill the tiny pores in the protective film, making it denser, thereby better preventing the invasion of the corrosive medium and reducing the occurrence of self-corrosion reactions. In addition, carbon nanotubes have a large specific surface area and can adsorb some active molecules in the corrosive medium. It can absorb oxygen molecules in the electrolyte solution, reduce the contact between oxygen and magnesium alloy, and thus reduce the rate of self-corrosion reaction. At the same time, it can also absorb and isolate some impurity ions that may accelerate self-corrosion.

[0024] In a second aspect, the present invention provides a method for preparing the sacrificial anode material as described above, comprising the following steps: Pure zinc, pure titanium, pure indium, pure cerium, pure lanthanum, pure gadolinium and pure magnesium are weighed and vacuum smelted until melted, a functional enhancer is added and electromagnetically stirred, stirred for 10-30 minutes, and then cooled to obtain a precursor, and the precursor is rolled and heat treated to obtain a sacrificial anode material.

[0025] In a preferred embodiment, the vacuum degree is ≤1x10 -3 Pa, the melting temperature is 400-800℃.

[0026] In a preferred embodiment, the heat treatment conditions are: stress relief at 150°C for 24 hours, followed by aging at 250°C for 1-2 hours, and finally aging at 200°C for 10-20 hours.

[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. In the present invention, the current efficiency of the material is significantly improved and the occurrence of self-corrosion reaction is reduced by compounding rare earth elements and metal elements.

[0028] 2. The present invention directly prepares nitrogen-doped spiral carbon nanofibers through electrospinning technology, and in situ generates carbon nanotubes on the nitrogen-doped spiral carbon nanofibers, so that the carbon nanotubes are directly embedded in the surface of the spiral carbon nanofibers, thereby preventing the agglomeration and phase separation of the two structures when the two are directly mixed, and further synergizes with various elements to improve the current efficiency of the material and reduce the occurrence of self-corrosion reactions of the material. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available.

[0031] Carbon nanotubes, with an average particle size of 200 mesh, were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0032] Nitrogen-doped helical carbon nanofibers with an average particle size of 200 mesh were purchased from Hunan Jidian Teineng Technology Co., Ltd.

[0033] Polyacrylonitrile, with an average molecular weight of 10,000, was purchased from Shanghai Hansi Chemical Co., Ltd.

[0034] Example 1 This embodiment provides a method for preparing a sacrificial anode material, comprising the following steps: (1) Preparation of functional enhancers In parts by mass, 1 part of polyacrylonitrile and 100 parts of N,N-dimethylformamide are mixed and stirred at a stirring temperature of 50°C for 4 hours, and then 20 parts of nickel acetate are added for electrostatic spinning. Specifically, the above liquid phase is loaded into a disposable syringe, and transported by a syringe pump at a constant flow rate of 0.3 ml / h, a grounded aluminum foil is used as a collector, and the distance between the needle tip and the aluminum foil is maintained at 15 cm. A DC voltage of 20 kV is applied between the needle tip and the aluminum foil to obtain electrostatically spun fibers, and then the fibers are kept at a temperature of 220°C for 1.5 hours for heat stabilization to obtain a solid phase. After mixing 1 part of the solid phase with 1.5 parts of melamine, the mixture is reacted at a temperature of 700°C for 2 hours under an argon atmosphere, and then acetylene gas is introduced to react at a temperature of 750°C for 20 minutes, and the fibers are cooled, washed, and ground through a 200-mesh sieve to obtain a functional enhancer.

[0035] (2) Preparation of sacrificial anode materials By mass, 4.24 parts of pure zinc, 2.07 parts of pure titanium, 0.68 parts of pure indium, 0.34 parts of pure cerium, 0.42 parts of pure lanthanum, 1.58 parts of pure gadolinium, and 82.73 parts of pure magnesium were weighed and vacuum smelted until melted, and the vacuum degree was 1×10 -3 Pa, the melting temperature is 600℃, 7.45 parts of functional enhancer are added and electromagnetic stirring is performed. After stirring for 15 minutes, the precursor is cooled and rolled and heat treated. First, stress relief is performed at 150℃ for 24 hours, then aging is performed at 250℃ for 1.5 hours, and finally aging is performed at 200℃ for 15 hours to obtain the sacrificial anode material.

[0036] Example 2 This embodiment provides a method for preparing a sacrificial anode material, comprising the following steps: (1) Preparation of functional enhancers In parts by mass, 1 part of polyacrylonitrile and 100 parts of N,N-dimethylformamide are mixed and stirred at a stirring temperature of 55°C for 4 hours, and then 20 parts of nickel acetate are added for electrostatic spinning. Specifically, the above liquid phase is loaded into a disposable syringe and transported by a syringe pump at a constant flow rate of 0.3 ml / h. A grounded aluminum foil is used as a collector, and the distance between the needle tip and the aluminum foil is maintained at 15 cm. A DC voltage of 20 kV is applied between the needle tip and the aluminum foil to obtain electrostatically spun fibers, and then the fibers are kept at a temperature of 280°C for 2.5 hours for heat stabilization to obtain a solid phase. After mixing 1 part of the solid phase with 1.7 parts of melamine, the mixture is reacted at a temperature of 750°C for 2 hours under an argon atmosphere, and then acetylene gas is introduced to react at a temperature of 850°C for 20 minutes. The fibers are cooled, washed, and ground through a 200-mesh sieve to obtain a functional enhancer.

[0037] (2) Preparation of sacrificial anode materials By mass, 6.13 parts of pure zinc, 2.87 parts of pure titanium, 1.05 parts of pure indium, 0.48 parts of pure cerium, 0.61 parts of pure lanthanum, 2.02 parts of pure gadolinium, and 76.83 parts of pure magnesium were weighed and vacuum smelted until melted, with a vacuum degree of 1×10 -3 Pa, the melting temperature is 700℃, 10.01 parts of functional enhancer are added and electromagnetic stirring is performed. After stirring for 20 minutes, the precursor is cooled and rolled and heat treated. First, stress relief is performed at 150℃ for 24 hours, then aging is performed at 250℃ for 2 hours, and finally aging is performed at 200℃ for 18 hours to obtain the sacrificial anode material.

[0038] Comparative Example 1 The difference between this comparative example and Example 1 is that pure zinc is not added, and the mass fraction of pure magnesium is changed to 86.57 parts.

[0039] Comparative Example 2 The difference between this comparative example and Example 1 is that pure titanium is not added, and the mass fraction of pure magnesium is changed to 84.8 parts.

[0040] Comparative Example 3 The difference between this comparative example and Example 1 is that pure indium is not added, and the mass fraction of pure magnesium is changed to 83.41 parts.

[0041] Comparative Example 4 The difference between this comparative example and Example 1 is that pure cerium is not added, and the mass fraction of pure magnesium is changed to 83.07 parts.

[0042] Comparative Example 5 The difference between this comparative example and Example 1 is that pure lanthanum is not added, and the mass fraction of pure magnesium is changed to 83.15 parts.

[0043] Comparative Example 6 The difference between this comparative example and Example 1 is that pure gadolinium is not added, and the mass fraction of pure magnesium is changed to 84.31 parts.

[0044] Comparative Example 7 The difference between this comparative example and Example 1 is that no functional enhancer is added, and the mass fraction of pure magnesium is changed to 90.18 parts.

[0045] Comparative Example 8 The difference between this comparative example and Example 1 is that the functional enhancer is replaced by carbon nanotubes with an average particle size of 200 meshes.

[0046] Comparative Example 9 The difference between this comparative example and Example 1 is that the functional enhancer is changed to nitrogen-doped spiral carbon nanofibers with an average particle size of 200 meshes.

[0047] Comparative Example 10 The difference between this comparative example and Example 1 is that the functional enhancer is changed to a mixture of carbon nanotubes with an average particle size of 200 mesh and nitrogen-doped helical carbon nanofibers with an average particle size of 200 mesh, and the mass ratio of the two is 1:1.

[0048] Performance Testing The anodes obtained in the examples and comparative examples were installed on offshore oil and gas field equipment for testing. The electrochemical performance was tested, and the results are shown in Table 1.

[0049] Table 1 Performance test results Open circuit potential / VCSE <![CDATA[Actual capacitance / A·h·kg -1 > Current efficiency / % Consumption in corrosive environments Example 1 -0.854 798.6895 92.87 No obvious pits, even consumption Example 2 -0.813 802.5687 94.56 No obvious pits, even consumption Comparative Example 1 -9.541 754.2347 82.18 Pit formation and uneven consumption Comparative Example 2 -9.421 765.3587 83.45 Pit formation and uneven consumption Comparative Example 3 -9.468 758.3692 84.29 Pit formation and uneven consumption Comparative Example 4 -9.562 749.2578 83.36 Pit formation and uneven consumption Comparative Example 5 -9.457 750.2367 85.24 Pit formation and uneven consumption Comparative Example 6 -9.402 751.2541 83.17 Pit formation and uneven consumption Comparative Example 7 -9.436 756.3668 85.19 Pit formation and uneven consumption Comparative Example 8 -10.856 700.1475 70.23 Large pits appear and consumption is uneven Comparative Example 9 -10.734 702.2697 71.98 Large pits appear and consumption is uneven Comparative Example 10 -10.427 733.6397 78.54 Large pits appear and consumption is uneven From the above performance test results, it can be seen that Examples 1-2 have better current efficiency and lower probability of self-corrosion reaction, especially Example 2 has the most outstanding comprehensive performance, which is mainly due to the synergistic effect between the compounded elements and the functional enhancer of the present invention.

[0050] The comparative example does not adopt the necessary technical solution, resulting in its performance being significantly worse than that of the embodiment in the corresponding performance test. This better proves the irreplaceable nature of the specific technical solution of the present application in achieving technical effects and solving technical problems.

[0051] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A sacrificial anode material, characterized in that: The invention comprises the following components by weight: 3.24-7.28 parts of zinc, 1.22-3.43 parts of titanium, 0.54-1.27 parts of indium, 0.22-0.64 parts of cerium, 0.36-0.77 parts of lanthanum, 1.10-2.47 parts of gadolinium, 5.47-11.21 parts of a functional enhancer, and the balance is magnesium; The function enhancer is a spiral carbon nanofiber doped with carbon nanotubes.

2. The sacrificial anode material according to claim 1, characterized in that: The material comprises the following components by weight: 4.24-6.13 parts of zinc, 2.07-2.87 parts of titanium, 0.68-1.05 parts of indium, 0.34-0.48 parts of cerium, 0.42-0.61 parts of lanthanum, 1.58-2.02 parts of gadolinium, 7.45-10.01 parts of a functional enhancer, and the balance being magnesium.

3. The sacrificial anode material according to claim 1 or 2, characterized in that: The preparation method of the functional enhancer is as follows: Polyacrylonitrile and N,N-dimethylformamide are mixed and stirred, and then nickel acetate is added for electrostatic spinning to obtain electrostatically spun fibers, and then heat stabilization treatment is performed to obtain a solid phase, and the solid phase is mixed with melamine for a primary reaction, and then acetylene gas is introduced for a secondary reaction, and the functional enhancer is obtained by cooling, washing, grinding and sieving.

4. The sacrificial anode material according to claim 3, characterized in that: The mass ratio of polyacrylonitrile, N,N-dimethylformamide and nickel acetate is 1:(50-100):(5-20).

5. The sacrificial anode material according to claim 3, characterized in that: The stirring conditions are: stirring temperature is 40-60° C., and stirring time is 3-6 h.

6. The sacrificial anode material according to claim 3, characterized in that: The conditions of the heat stabilization treatment are: keeping the temperature at 200-300° C. for 1-3 hours.

7. The sacrificial anode material according to claim 3, characterized in that: The mass ratio of the solid phase to melamine is 1:(1.2-1.9).

8. The sacrificial anode material according to claim 3, characterized in that: The conditions of the primary reaction are: reacting at a temperature of 600-800° C. for 1-3 h under an argon atmosphere; And / or, the conditions of the secondary reaction are: reacting at a temperature of 700-900° C. for 15-40 min; And / or, the sieve used for the sieving is 100-300 meshes.

9. A method for preparing the sacrificial anode material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Pure zinc, pure titanium, pure indium, pure cerium, pure lanthanum, pure gadolinium and pure magnesium are weighed and vacuum smelted until melted, a functional enhancer is added and electromagnetically stirred, stirred for 10-30 minutes, and then cooled to obtain a precursor, and the precursor is rolled and heat treated to obtain a sacrificial anode material.

10. The method for preparing the sacrificial anode material according to claim 9, characterized in that: The vacuum degree is ≤1x10 -3 Pa, melting temperature is 400-800℃; And / or, the heat treatment conditions are: stress relief at 150° C. for 24 hours, followed by aging at 250° C. for 1-2 hours, and finally aging at 200° C. for 10-20 hours.

Citation Information

Patent Citations

  • High negative potential magnesium base alloy sacrificial anode material and application thereof

    CN101818351A

  • Sm-containing multielement magnesium alloy sacrificial anode material and preparation method thereof

    CN107142483A

  • High-potential sacrificial magnesium alloy anode and manufacturing method thereof

    CN101638786A

  • Alloy sacrificial anode film preventing stress corrosion cracking and preparation method thereof

    CN101928944A

  • Sacrificial anode material

    CN102605376A